The Impact of Taxation Socialization, Taxpayer Understanding, Service Quality, and Perception of Tax Rates on Individual Taxpayer Compliance - Murtin, Alex; Maryani, Yani; Ummah, Rizka Saniyatul (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims to objectively investigate how perceived tax rates, taxpayer comprehension, tax socialization, and service quality impact individual taxpayer compliance. This study uses the theory of planned behaviour. The theory of planned behaviour states that the behaviour carried out by a person is based on the will factor, which is used as a reason to perform the behaviour. Purposive sampling is one of the sampling strategies used in this study to obtain primary data. 120 respondents completed questionnaires, which were used to collect data. They are testing hypotheses with SPSS software. Based on the results of the SPSS analysis, taxpayer understanding and perceptions of tax rates affect individual taxpayer compliance. However, tax socialization and service quality do not affect individual taxpayer compliance. This research contributes to developing the Theory of Planned Behavior in the context of individual taxpayer compliance. This research references the Government and the Directorate General of Taxes in making policies to improve taxpayer compliance. However, this study only used a small sample, so the research results were less in-depth.